Interactive Effects of Elevated CO2 and N Fertilization on Yield and Quality of Tomato Grown Under Reduced Irrigation Regimes - Wei, Zhenhua; Du, Taisheng; Li, Xiangnan; Fang, Liang; Liu, Fulai (Frontiers in Plant Science, 2018)
The interactive effects of CO2 elevation, N fertilization, and reduced irrigation regimes on fruit yield and quality in tomato (Solanum lycopersicum L.) were investigated in a split-root pot experiment. The plants were grown in two separate climate-controlled greenhouse cells at atmospheric [CO2] of 400 and 800 ppm, respectively. In each cell, the plants were fertilized at either 100 or 200 mg N kg-1 soil and were either irrigated to full water holding capacity (i.e., a volumetric soil water content of 18%) (FI), or using 70% water of FI to the whole pot (DI) or alternately to only half of the pot (PRI). The yield and fruit quality attributes mainly from sugars (sucrose, fructose, and glucose) and organic acids (citric acid and malic acid) to various ionic (NH4+, K+, Mg2+, Ca2+, NO3-, SO42- and PO43-) concentrations in fruit juice were determined. The results indicated that lower N supply reduced fruit number and yield, whereas it enhanced some of the quality attributes of fruit as indicated by greater firmness, higher concentrations of sugars and organic acids. Elevated [CO2] (e[CO2]) attenuated the negative influence of reduced irrigation (DI and PRI) on fruit yield. Principal components analysis revealed that the reduced irrigation regimes, especially PRI, in combination with e[CO2] could synergistically improve the comprehensive quality of tomato fruits at high N supply. These findings provide useful knowledge for sustaining tomato fruit yield and quality in a future drier and [CO2]-enriched environment.